Low temperature plasma for the preparation of crater walls for compositional depth profiling of thin inorganic multilayers. (17th October 2016) - Muramoto, Shin; Bennett, Joe
Abstract : An indirect, compositional depth profiling of an inorganic multilayer system using a helium low temperature plasma (LTP) containing 0.2% (v/v) SF6 was evaluated. A model multilayer system consisting of four 10 nm layers of silicon separated by four 50 nm layers of tungsten was plasma‐etched for (10, 20, 30) s at substrate temperatures of (50, 75, and 100) °C to obtain crater walls with exposed silicon layers that were then visualized using time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) to determine plasma‐etching conditions that produced optimum depth resolutions. At a substrate temperature of 100 °C and an etch time of 10 s, the FWHM of the second, third, and fourth Si layers were (6.4, 10.9, and 12.5) nm, respectively, while the 1/e decay lengths were (2.5, 3.7, and 3.9) nm, matching those obtained from a SIMS depth profile. Though artifacts remain that contribute to degraded depth resolutions, a few experimental parameters have been identified that could be used to reduce their contributions. Further studies are needed, but as long as the artifacts can be controlled, plasma etching was found to be an effective method for preparing samples for compositional depth profiling of both organic and inorganic films, which could pave the way for an indirect depth profile analysis of inorganic–organic hybrid structures that have recently evolved into innovative next‐generation materials. Copyright © 2016 John Wiley & Sons, Ltd.